A statistical simulation model to guide the choices of analytical methods in arrayed CRISPR screen experiments. - Chang Sik Kim; Jonathan Cairns; Valentina Quarantotti; Bogumil Kaczkowski; Yinhai Wang; Peter Konings; Xiang Zhang (PLoS ONE)
An arrayed CRISPR screen is a high-throughput functional genomic screening method, which typically uses 384 well plates and has different gene knockouts in different wells. Despite various computational workflows, there is currently no systematic way to find what is a good workflow for arrayed CRISPR screening data analysis. To guide this choice, we developed a statistical simulation model that mimics the data generating process of arrayed CRISPR screening experiments. Our model is flexible and can simulate effects on phenotypic readouts of various experimental factors, such as the effect size of gene editing, as well as biological and technical variations. With two examples, we showed that the simulation model can assist making principled choice of normalization and hit calling method for the arrayed CRISPR data analysis. This simulation model is implemented in an R package and can be downloaded from Github.